ChemInform Abstract: Mesoporous and Hexagonally Ordered CuAl‐SBA‐15‐Catalyzed Tandem C—C and C—O Bond Formation Between Phenols and Allylic Alcohols. Issue 3 (22nd January 2013) - Varghese, Shaji; Anand, Chokkalinkam; Dhawale, Dattatray; Mano, Ajayan; Balasubramanian, Veerappan V.; Raj, George Allen Gnana; Nagarajan, Samuthira; Wahab, Mohammad A.; Vinu, Ajayan
Abstract A novel reusable mesoporous catalyst incorporating Cu and Al with a hexagonally ordered structure is prepared and applied to the annulation of phenols with allylic alcohols to yield dihydrobenzopyrans.